Leisure and happiness among teachers - Nur Hidayah, Khozed (Universiti Malaysia Sarawak (UNIMAS), 2019)
Most researches are focus on stress and workload faced by the teachers but there is least of researches work on leisure among teachers. Getting involve in leisure activities and have a great satisfaction on it will create a high level of happiness of individuals. This research will examine the relationship between leisure involvement and leisure satisfaction towards happiness among the teachers. This study was conducted using quantitative study and questionnaire as an instrument to collect the data from the respondents. The sample of this study involved 106 teachers from two secondary school in Alor Setar, Kedah which has been selected through convenience sampling method. Pearson Correlation was used to analyse the strength of each hypothesis and the result shows leisure involvement and leisure satisfaction have a significant relationship towards happiness among the teachers. Therefore, teachers need to participate or having more leisure activities in their free time as it contributes to their physical, mental health and also happiness.